2022
DOI: 10.1128/spectrum.03069-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Trait Variation of the Opportunistic Human Pathogen Aspergillus flavus and Its Close Relatives

Abstract: Aspergillus flavus is a filamentous fungus that causes opportunistic human infections, such as aspergillosis and fungal keratitis, but its close relatives are considered nonpathogenic. To begin understanding how this difference in pathogenicity evolved, we characterized variation in infection-relevant genomic, chemical, and phenotypic traits between strains of A. flavus and its relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 135 publications
1
8
0
Order By: Relevance
“…Nevertheless, our molecular identification results indicated that A. nomiae AnS1Gzl-1 is more closely related to A. pseudonomiae (a non-pathogenic pathogen) in evolution, while it is more distant from A. flavus . The results are similar to a previous study from Hatmaker et al (2022) . There were only 46 secondary metabolite gene synthesis clusters related to the infection in its genome and it was 16–20 fewer compared with that in the pathogenic A. flavus .…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, our molecular identification results indicated that A. nomiae AnS1Gzl-1 is more closely related to A. pseudonomiae (a non-pathogenic pathogen) in evolution, while it is more distant from A. flavus . The results are similar to a previous study from Hatmaker et al (2022) . There were only 46 secondary metabolite gene synthesis clusters related to the infection in its genome and it was 16–20 fewer compared with that in the pathogenic A. flavus .…”
Section: Discussionsupporting
confidence: 92%
“…Our interest in the fungal UPR as a potential virulence determinant in the cornea was therefore based on two simple and connected hypotheses: first, that A. fumigatus upregulates the expression of various secreted proteases in vivo and, second, that an upregulation in secretion would lead to ER stress and activate the iUPR as determined by increased hacA splicing above baseline. To confirm these predictions, we employed an epithelial abrasion model of FK developed and previously reported by our group [26,34]. Briefly, C57BL/6J mice were immunosuppressed with a single treatment of methylprednisolone on the day preceding inoculation.…”
Section: Resultsmentioning
confidence: 97%
“…For the comparative analysis of inhibitory effects resulting from fungal contaminations on both EO-NE-PW and PW substrates, the Kirby-Bauer assay was employed, and the pre-sterilized samples (in the agar) were monitored for fungal growth over a 10-day period. For this assay we use A. flavus , one of the common species in the saprophytic filamentous fungal genus Aspergillus known to cause black molds in red apples ( Alegbeleye et al, 2022 ; Hatmaker et al, 2022 ; Keykhosravi, 2018 ). It is an accepted phenomenon that the clear zone (zone of inhibition) formed around the filter paper is attributable to the presence of antifungal materials within the filter paper.…”
Section: Resultsmentioning
confidence: 99%